Dirty Density: Air Quality and the Density of American Cities - Felipe Carozzi; Sefi Roth (Institute of Labor Economics (IZA), 2020)
In this paper we study the effect of urban density on the exposure of city dwellers to air pollution using data from the United States urban system. Exploiting geological features to instrument for density, we find an economically and statistically significant pollution-density elasticity of 0.13. We also assess the health implications of these estimates and find that doubling density in an average city increases annual mortality costs by 630 per capita. Our findings highlight the possible trade-off between reducing global greenhouse gas emissions, which is associated with denser cities according to prior research, and preserving local air quality and human health within cities.
Keywords: Q53; R11; I10; 330; air pollution; cities; density; health